Temperature-Sensitive Defect of Mutants Isolated from L Cells Persistently Infected with Newcastle Disease Virus - Preble, Olivia T. (1973)
The temperature-sensitive defects of virus mutants isolated from L cells persistently infected with Newcastle disease virus (NDV) were analyzed. Genetic grouping of the mutants by complementation tests was attempted by using several different methods, including yield analysis, RNA synthesis, and heterozygote formation at 42 to 43 C, the nonpermissive temperature. In each case, specific interference prevented detection of complementation. This interference was shown to occur prior to or at the level of virus RNA synthesis. Temperature-shift experiments with five different NDV(pi) clones showed that virus replication begun at 37 C could not be completed at the nonpermissive temperature. The activity of the NDV-specific RNA-dependent RNA polymerase in the cytoplasm of infected chicken embryo cells was not stable and could not be demonstrated directly. However, indirect measurement of RNA polymerase activity at the nonpermissive temperature was accomplished by studying the kinetics of virus-specific RNA synthesis in infected cells after temperature shift. Two types of response were obtained: with three NDV(pi) clones, virus-specific RNA synthesis ceased immediately upon transfer of infected cells to 42 to 43 C, whereas in cells infected with two other NDV(pi) clones, RNA synthesis continued for several hours at this temperature. These results suggested that there may be two types of ts defects in NDV(pi), both associated with virus-specific RNA polymerase activity.